Coral reef conservation in the Anthropocene: Confronting spatial mismatches and prioritizing functions. (August 2019) - Bellwood, David R.; Pratchett, Morgan S.; Morrison, Tiffany H.; Gurney, Georgina G.; Hughes, Terry P.; Álvarez-Romero, Jorge G.; Day, Jon C.; Grantham, Ruby; Grech, Alana; Hoey, Andrew S.; Jones, Geoffrey P.; Pandolfi, John M.; et al.
Abstract: The world's coral reefs are rapidly transforming, with decreasing coral cover and new species configurations. These new Anthropocene reefs pose a challenge for conservation; we can no longer rely on established management plans and actions designed to maintain the status quo when coral reef habitats, and the challenges they faced, were very different. The key questions now are: what do we want to conserve on Anthropocene reefs, why, and how? Trends in reef management over recent decades reveal rapid shifts in perceived threats, goals and solutions. Future reefs will be unlike anything previously seen by humans, and while their ability to support tourism or fisheries may be relatively resilient, our capacity to manage them may be constrained by their new species configurations. Furthermore, there is a growing spatial mismatch between the escalating scale of threats and current or planned responses. We present a blueprint for future reef conservation that recognizes the need to better understand the processes that maintain Anthropocene reefs, and the growing imperative to reform conservation efforts to address both specific local issues and larger-scale threats. The future of coral reef conservation is no longer one solely of localized action and stewardship; it requires practices and institutions operating at far larger scales than today. Highlights: The key questions are: what do we want to conserve on coral reefs, why and how? We identify scale mismatches between reef stressors and proposed interventions. Anthropocene reefs require a re-prioritization of critical functions. The scale of institutions and governance needs to match the scale of stressors. Cosmetic conservation will not combat the coral reef crisis.